Atypical kawasaki disease with polymyositis and panniculitis: Case report and review of literature - Raajashri Rajasegar; Kiruthiga Sugumar; Venkatesh Chandrasekaran; Dhandapany Gunasekaran; Avinash Anantharaj (Wolters Kluwer Medknow Publications, 2022)
Background: Kawasaki disease (KD) is a medium-vessel vasculitis that commonly affects young children. Many atypical presentations that differ from the classical phenotype have been described. Clinical Description: A 3-year-old boy presented with acute onset refusal to walk due to severe pain in both lower limbs for 8 days. This was accompanied by fever for 7 days. Significant findings included diffuse tenderness of bilateral thighs and leg muscles, probable normal joints, and absence of rashes, edema, significant lymphadenopathy, organomegaly, or paralysis. He had a hemoglobin of 10.6 g/dL, neutrophilic leukocytosis, and normal platelet count (384 × 109/L). He was started on intravenous cloxacillin, assuming polymyositis or acute osteomyelitis. Radiographs, ultrasonography, and bone scan of the lower limbs revealed normal bones and joints. However, magnetic resonance imaging detected patchy hyperintensities in multiple muscles, though muscle-specific enzyme levels were normal. The fever and pain persisted and investigations for other differentials (including classical KD) were inconclusive. At the end of 2nd week of illness, atypical KD was suspected, when he developed periungual skin peeling with increasing erythrocyte sedimentation rate and platelet counts. Management: The diagnosis was confirmed by echocardiogram proven left main coronary artery dilatation. He was started on intravenous immunoglobulin. Since fever persisted, a second dose was administered, following which defervescence occurred and his symptoms subsided. Conclusions: Atypical KD should be considered in a fever of unknown origin when diagnostic criteria of classical KD are not satisfied. Polymyositis and panniculitis are uncommon atypical manifestations.